2022
DOI: 10.1007/s00115-022-01411-1
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis—An update

Abstract: ZusammenfassungDer Nachweis von Autoantikörpern gegen Nerven- oder Gliazellen ermöglicht heute bei zahlreichen neurologischen und psychiatrischen Symptomkomplexen die frühe und spezifische Diagnose einer Autoimmunenzephalitis. Damit hat sich auch die Herangehensweise an die immuntherapeutische Behandlung dieser Krankheitsgruppe fundamental verändert, ebenso wie das Verständnis der zugrunde liegenden Pathophysiologie und der auslösenden Faktoren. Die noch immer wachsende Zahl neuer Autoantikörper erfordert ein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
6
0
1
Order By: Relevance
“…This study raises the number of published laboratory-confirmed human BoDV-1 infections to 46 (Table 1), following the case definition of Eisermann et al 11 , which requires direct virus from the patient. Twenty-eight cases were confirmed by RT-qPCR during this study (including previously published cases without BoDV-1 sequence; 7,9,14,16,17,18,65,66,67 ). BoDV-1 sequences were available from public databases for further 16 previously published human cases (Table 1) 6,7,8,10,11,12,13,15 .…”
Section: Bodv-1 Infections In Domestic Mammals and Humanssupporting
confidence: 58%
See 3 more Smart Citations
“…This study raises the number of published laboratory-confirmed human BoDV-1 infections to 46 (Table 1), following the case definition of Eisermann et al 11 , which requires direct virus from the patient. Twenty-eight cases were confirmed by RT-qPCR during this study (including previously published cases without BoDV-1 sequence; 7,9,14,16,17,18,65,66,67 ). BoDV-1 sequences were available from public databases for further 16 previously published human cases (Table 1) 6,7,8,10,11,12,13,15 .…”
Section: Bodv-1 Infections In Domestic Mammals and Humanssupporting
confidence: 58%
“…Our study increases the number of published laboratory-confirmed human BoDV-1-infections to 46 and provides a first comprehensive summary of metadata for all published cases 6,7,8,9,10,11,12,13,14,15,16,17,18 . The cases covered all age groups and encephalitis was diagnosed for 45 of the 46 patients, of -25 -whom 44 had died as a result of the disease, resulting in a known case-fatality rate of 97.8%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Anti-NMDAR antibodies of the immunoglobulin subtypes IgA, IgG, or IgM were detected in 30% of patients during HSE, suggesting secondary autoimmune mechanisms. The presence of these antibodies is associated with classic autoimmune encephalitis in most patients, though notably some patients who developed anti-NMDAR antibodies after HSE did not clinically develop autoimmune encephalitis [ 118 ]. Typically, patients with later develop autoimmune encephalitis have symptoms within the first two months after HSV encephalitis, however, a delayed onset up to a year has been reported [ 118 ].…”
Section: Advances In Ischemic Stroke and Intracerebral Hemorrhagementioning
confidence: 99%